Analysis of the State and Trends of Ukraine’s Foreign Trade with the EU - BulakhТ. M.; IvashchenkoО. A.; Plakhotnikova, L. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Presently, Ukraine is highly integrated into the global economic area and maintains foreign trade relations with more than 200 countries. The European Union (EU) is one of the most important foreign trade partners of Ukraine. Therefore, the analysis of Ukraine’s foreign trade is important for taking effective management decisions and promoting reasonable changes in the economic policy. The article analyzes the state and trends of Ukraine’s foreign trade with the EU. Its features and dynamics are revealed. The changes in the structure of exports and imports of Ukraine after the signing of the Free Trade Agreement are as follows: export values reaching the pre-crisis level of 2014; the sustained dominance of agricultural and food industry products; the commodity structure of exports could be diversified; imports of goods to Ukraine from the EU in 2012–2017 decreased at a slower pace than the total imports of goods to Ukraine; after a negative trend in 2012–2015, the imports increased by 3658.5 million USD in 2017, signaling that the imports to Ukraine from the EU were recovering at a faster pace than the Ukrainian exports to the EU; the balance of foreign trade in goods between Ukraine and the EU for the period of the study was negative. Measures to improve the development of foreign trade of Ukraine in the context of deepening European integration processes are proposed: to increase the support for national producers; to intensify export cooperation with the EU member states with which Ukraine has a negative balance; to attract exporters from non-EU countries to locate production facilities on the territory of Ukraine with the prospects of their exports to European markets; to introduce uniform standards of certification and standardization of products in Ukraine; to develop a strategy to increase exports of nationally produced goods and services to EU markets and reduce imports to Ukraine; to intensify cooperation with the EU on issues of import substitution in Ukraine.